2018
DOI: 10.1111/jfb.13647
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of the timing and degree of smolt development in southern populations of masu salmon Oncorhynchus masou

Abstract: The present study assessed whether non-anadromous masu salmon Oncorhynchus masou in Miyazaki, southern Japan, smoltify, and if so, at what time of the year. Yearling O. masou of Miyazaki and an anadromous population from Hokkaido, northern Japan, were reared in hatcheries in their respective regions and sampled monthly from February to June to examine the spring smoltification period. The Hokkaido population showed a peak of gill Na -K -ATPase (NKA) activity in May, which was accompanied with an increase in mR… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 44 publications
0
3
0
Order By: Relevance
“…Downregulation of the α1a subunit and upregulation of the α1b occur while the fish are still in fresh water and this occurs prior to the increase in NKA activity in S. trutta (Seidelin et al ., ), indicating that the migration destination is pre‐determined. Non‐anadromous Oncorhynchus masou (Brevoort 1856) were found to show an increase in NKA activity in smolt‐like individuals but, unlike anadromous individuals, this was not accompanied by an increase in the α1b isoform (Inatani et al ., ).…”
Section: Causes and Consequences Of Life‐history Decisionsmentioning
confidence: 97%
See 1 more Smart Citation
“…Downregulation of the α1a subunit and upregulation of the α1b occur while the fish are still in fresh water and this occurs prior to the increase in NKA activity in S. trutta (Seidelin et al ., ), indicating that the migration destination is pre‐determined. Non‐anadromous Oncorhynchus masou (Brevoort 1856) were found to show an increase in NKA activity in smolt‐like individuals but, unlike anadromous individuals, this was not accompanied by an increase in the α1b isoform (Inatani et al ., ).…”
Section: Causes and Consequences Of Life‐history Decisionsmentioning
confidence: 97%
“…Although often seen only as a preparation for anadromy, there is increasing evidence that many similar changes occur for potamodromous migrants. Thus, increase in NKA activity, widely used as an indicator of anadromous smoltification, occurs also in potamodromous migrants (Boel et al ., ; Inatani et al ., ), as do changes in behaviour, skin pigmentation and body morphology (Table ). Whether this increase in NKA in potamodromous migrants has functional significance or simply reflects ancestral standing genetic variation is not known.…”
Section: Causes and Consequences Of Life‐history Decisionsmentioning
confidence: 99%
“…Inatani et al . () found that anadromous O. masou from the north of Japan had increased gill Na + –K + ‐ATPase activity and salinity tolerance in spring, whereas fish from landlocked populations in the south did not change in spring but showed modest increases in smolt appearance and salinity tolerance in autumn. It is less clear if populations in the same river catchment have evolved differential traits related to smolt development.…”
mentioning
confidence: 99%